Electrodeposition of partially oxidized tetracyanoplatinate nanowires on seeds and patterns for gas sensing. Issue 8 (15th November 2017) - Jahanian, Pedram; Yu, Xuecheng; Kilani, Mohamed; Mao, Guangzhao
ABSTRACT: This paper describes the synthesis of a new type of nanowires, potassium tetracyanoplatinate sesquihydrate Krogmann salt or K( def )TCP. Seed-mediated electrocrystallization nucleates and confines the K( def )TCP crystals into nanowires. Our data show that the width of K( def )TCP scales proportionally with the diameter of the seed, which is consistent with the nanoconfinement effect of the seed. K( def) TCP nanowires are also electrodeposited on lithographic Au patterns as interconnects and tested for impedance-based gas sensing. The results demonstrate the use of electrocrystallization to construct nanowire sensing units directly on patterned substrates to enable scaling up of nanowire sensor technology. IMPACT STATEMENT We show for the first time nanowires directly formed as interconnects on electronic substrates by electrocrystallization are used as sensor materials to detect gases. GRAPHICAL ABSTRACT: